Criteria-based audit to improve a district referral system in Malawi: A pilot study - Mlava Grace; Kongnyuy Eugene J; Broek Nynke (BMC, 2008)
Abstract Background To study the feasibility of using criteria-based audit to improve a district referral system. Methods A criteria-based audit was used to assess the Salima District referral system in Malawi. A retrospective review of 60 obstetric emergencies referred from 12 health centres was conducted and compared with prior established standards for optimal referral of emergencies. Recommendations were made and implemented. Three months later, a re-audit was conducted (62 cases). Results There were significant improvements in 4 out of 7 standards: adequate resuscitation before referral (33.3% vs 88.7%; p = 0.001); delay of less than 2 hours from the time the ambulance is called to when the ambulance brought the patient to the hospital (42.8% vs 88.3%; p = 0.014); clinician attends to patient within 30 minutes of arrival to hospital (30.8% vs 92.6%; p = 0.001) and feedback given to the referring health centres (1.7% vs 91.9%; p <0.001). The rest of the three standards showed a high level of attainment (>95%) in both the initial audit and the re-audit: referred patients accompanied by a referral form; ambulances are available at all times and the district hospital is informed through short-wave radio by the health centre when a patient is referred. Conclusion Criteria-based audit can improve the ability of a district referral system to handle obstetric emergencies in countries with limited resources.